Investigation of the absorption Ångström exponent and its relation to physicochemical properties for mini-CAST soot. Issue 7 (3rd July 2018) - Török, Sandra; Malmborg, Vilhelm B.; Simonsson, Johan; Eriksson, Axel; Martinsson, Johan; Mannazhi, Manu; Pagels, Joakim; Bengtsson, Per-Erik
ABSTRACT: In this work, a mini-CAST soot generator was used to produce soot with different optical and physicochemical characteristics. Absorption Ångström exponents ( AAE ) expressing the absorption wavelength dependence were assessed by multiwavelength in-situ and filter-based (aethalometer) laser extinction. The two optical techniques showed good agreement. For the chosen mini-CAST operating conditions, AAE s between 1 and 3.5 were found. Soot with high mass-fractions of organic carbon (OC) and pyrolytic carbon (PC) determined with thermal optical analysis were associated with AAE s significantly higher than 1. Heating to 250 and 500°C removed the majority of polycyclic aromatic hydrocarbons. However, the thermal-optical analysis revealed that OC and PC were abundant in the soot with AAE > 2 also after heating the aerosol. Analysis of mass absorption cross section ratios for elemental carbon and OC indicated that elevated AAEs also after heating to 500°C could be related to persistent OC and PC components and/or the refractory soot. By comparing the mini-CAST soot optical properties with soot properties derived from in-situ extinction measurements in a premixed flame, mini-CAST soot with a higher AAE could be identified as less mature soot. Copyright © 2018 The Authors